1988
DOI: 10.1182/blood.v72.2.436.436
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of the immunotype in diffuse large-cell lymphoma: a comparative study of the T-cell and B-cell phenotype

Abstract: The clinical significance of immunophenotyping of the non-Hodgkin's lymphomas is controversial. Therefore, we conducted the present study of 103 consecutively accrued diffuse large-cell lymphoma (DLCL) patients to define, independently of histologic subtypes, the prognostic importance of phenotyping. We used an extensive panel of monoclonal antibodies to T- and B-cell antigens to assign all patients immunologically into the T-cell (20 patients) or B-cell group (83 patients). The only significant differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…From a clinical point of view, PTCL is considered an aggressive malignancy, and in agreement with this characterization, many investigators have found the T‐cell phenotype to be an independent adverse prognostic factor2, 3, 9; others, however, have been unable to confirm this finding 10–13. PTCL is no longer included in the WHO classification system, and the significant clinical heterogeneity of malignancies that fall under the umbrella of PTCL has been emphasized.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…From a clinical point of view, PTCL is considered an aggressive malignancy, and in agreement with this characterization, many investigators have found the T‐cell phenotype to be an independent adverse prognostic factor2, 3, 9; others, however, have been unable to confirm this finding 10–13. PTCL is no longer included in the WHO classification system, and the significant clinical heterogeneity of malignancies that fall under the umbrella of PTCL has been emphasized.…”
mentioning
confidence: 87%
“…In addition, a new subclass of PTCL has been identified and appropriately termed peripheral T‐cell lymphoma, unspecified ( PTCL‐U ); however, this is a blanket term that is used to describe a heterogeneous array of lymphomas with differing clinical features, histologic characteristics, genetic alterations, responses to treatment, and associated prognoses. The complex nature of PTCL is evident,2, 3, 9–24 but various indicators can assist in the prediction of a given PTCL's clinical course. In this context, the International Prognostic Index (IPI),25 which was developed for the assessment of aggressive lymphomas, represents a possible foundation on which to base a more appropriate clinical definition of PTCL‐U 26.…”
mentioning
confidence: 99%
“…The explanation for the discrepancy between the two series is unclear, but the high percentage of AILs in the Hong Kong experience is one possible explanation. When compared with B‐cell lymphomas, T‐cell lymphomas have been reported to have a significantly worse recurrence free survival and OS when treated with combination chemotherapy 46, 47. In addition, Aviles et al reported that the presence of angiocentric features in sinonasal lymphomas predict for lower recurrence free survival when treated by XRT alone as well as an inferior salvage rate with combination chemotherapy 39…”
Section: Discussionmentioning
confidence: 99%
“…Large cell NHL are the most common subtypes, and 80-88% express B cell lineage antigens (43,44,45). The WF recognizes 3 morphologic subtypes: D-M and D-L of follicular center cell origin, and IB of nonfollicular center cell origin.…”
Section: Diffuse Large Cell Lymphomas (B Cell Nhl)mentioning
confidence: 99%